ANALISIS PENGARUH KUALITAS LAYANAN TERHADAP KEPUASAN KONSUMEN DI AJB BUMIPUTERA PURWOKERTO - Hogy Hedo Bramantika, 10.05.51.0099; Kasmari, Kasmari (Students Journal of Economic and Management, 2014)
This study examine about the influance of service quality on customer satisfaction. Service quality is action which given to the customer so as to give the good impression, so the customer have a good positive opinion to the firm. Service quality consist of dimensions such as tangible, reliability, responsiveness, assurance, and empathy.Keyword : service quality and cutomer satisfaction